Effect power transmission by flexible fixed and moving on some of the variables earth-strikes for players of tennis team Anbar University - Mahmoud , Shaker (Journal of Physical Education, 2011)
Extract study: The problem lies in the performance of earth-strikes of the upper limb joints, and sometimes just a simple rotation of the torso, which makes the performance of our students and our players ineffective for failing to reinvest the transfer of power between all parts of the body which requires rehearsed performance flexible to address this weakness, The study aims to invest in the transfer of power by flexible fixed and moving, and knowledge of its impact on some of the variables earth- strikes with the hypothesis that the power transfer of the variables earth-strikes in tennis between the pre-testing and post, Adopted the experimental method to study and design of the experimental group and one on a sample of eight students, The field procedures were test before me on Thursday (21/10/2010) in (10:30) o'clock am on the pitch outside of tennis, as the implementation of special exercises for the transfer of powers over the nine weeks, and by two units a week, was a post-test on Sunday (26/12/2010) on the same pitch and the same conditions to test tribal, To conclude that the transfer of powers to develop some of the variables strikes earth stations, especially the strike force and speed, and certainly recommend a researcher on the transfer of powers to earth-strikes by quality exercises and the rest of the skills of tennis and other games.